Assessment of plasma insulin, c-peptide, and blood pressure parameters of type 1 and type 2 diabetes mellitus and diabetic complications (Journal of Pathology of Nepal, 2020)
Background: Regardless of the type of diabetes mellitus, there is always a Beta-cell dysfunction leading to absolute insulin deficiency in type 1 diabetes mellitus or associated with insulin resistance in case of type 2 diabetes mellitus.Materials and Methods: A total of 267 subjects consisting of 164 diabetic patients and 103 non-diabetic apparently healthy individuals were analysed. The plasma insulin and c-peptides levels were determined using enzyme link immunosorbent assay, while plasma glucose level was determined using standard spectrophotometric method.Results: The biochemical results showed that the mean plasma glucose of Type 1 diabetes (213.65±20.35) and Type 2 diabetes (218.78+7.85) were significantly (P0.05) differences in the mean plasma c-peptide level, systolic and diastolic readings of Diabetic patients with coronary heart disease or retinopathy.Conclusion: There were significant differences in the blood pressure parameters in both the diabetes mellitus and diabetic complications in this study.